2016
DOI: 10.1002/hed.24424
|View full text |Cite
|
Sign up to set email alerts
|

Transoral laser microsurgery as primary treatment for selected T3 glottic and supraglottic cancers

Abstract: TLM ± selective neck dissection ± adjuvant (chemo)radiotherapy for selected T3 glottic and supraglottic SCC represents an effective alternative treatment to open partial laryngectomies and nonsurgical organ preservation protocols, particularly in elderly and frail patients. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1107-1112, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
5
23
0
Order By: Relevance
“…This is the reason why close cooperation with expert pathologists is of overwhelming importance. In accordance with these strict indications for adjuvant treatment, some authors such as Wilkie, Pearson and Peretti [34][35][36]42] gained the highest rates of OS and DFS, in contrast to Hinni et al [32], thus highlighting that TLM might reach excellent results when accurate selection of patients is made. Whilst, articles about closed technique showed less homogeneity in their outcome results, papers dealing with open procedures obtained more comparable data.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is the reason why close cooperation with expert pathologists is of overwhelming importance. In accordance with these strict indications for adjuvant treatment, some authors such as Wilkie, Pearson and Peretti [34][35][36]42] gained the highest rates of OS and DFS, in contrast to Hinni et al [32], thus highlighting that TLM might reach excellent results when accurate selection of patients is made. Whilst, articles about closed technique showed less homogeneity in their outcome results, papers dealing with open procedures obtained more comparable data.…”
Section: Discussionmentioning
confidence: 97%
“…Closed techniques differed from the open ones in proposing a second surgical revisions in case of first pathological report indicative for presence of invasive cancers on resection margins; while, in the case of equivocal margins second procedures were not routinely performed. Only after a second pathological report indicative for deep positive margins, adjuvant RT was administered on the primary tumour site [35,36,42]. This is the reason why close cooperation with expert pathologists is of overwhelming importance.…”
Section: Discussionmentioning
confidence: 99%
“…7 Many series have reported the outcomes of TLM in laryngeal cancer, pointing out some of the risks and complications of this type of surgery. [12][13][14][15][16][17][18] With such controversial evidence, it is difficult sometimes to decide between TLM and other therapeutic approaches. 11 For this reason, some authors recommend TLM only in early or selected intermediate cases, 11 whereas others have published large series with good results in locally advanced cases.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the idea of organ preservation, TLM and open/endoscopic partial laryngectomies have been proposed as therapeutic alternatives to radiotherapy or chemoradiotherapy in several publications [28,29]. Canis et al and Peretti and colleagues have reported five-year OS of 64.4% and 63.3% in two studies where TLM was used as the primary approach to T3 glottic and supraglottic LSCC, respectively [30,31]. Both authors highlighted the favorable functional outcome but stressed the importance of careful patient selection.…”
Section: Discussionmentioning
confidence: 99%